Research Advances on Exercise Intervention for Obesity Comorbid with Hyperlipidemia - Liu, Nianshuo Liu; Xu, Jianan; Liu, Ziyin; Li, Cuihan; Zhang , Jianwei; Lyu , Shaojun (The Journal of the International Society of Chinese Health Practices, 2025)
See PDF for details